Author Correction: Thermal transport crossover from crystalline to partial-crystalline partial-liquid state - Yanguang Zhou (Nature Portfolio, 2018)
The original version of this Article incorrectly omitted an affiliation of Sebastian Volz: ‘LIMMS/CNRS-IIS(UMI2820) Institute of Industrial Science, University of Tokyo 4-6-1 Komaba, Meguro-ku Tokyo 153-8505 JAPAN’. This has now been corrected in both the PDF and HTML versions of the Article.